Association of MMP3, MMP14, and MMP25 gene polymorphisms with cerebral stroke risk: a case-control study - Yanling Yin; Yu Zhang; Xiaobo Zhang; Qi Zhang; Jiachen Wang; Tian Yang; Chen Liang; Wu Li; Jie Liu; Xiaojuan Ma; Jinwei Duan; Wenzhen Shi; et al. (BMC, 2023)
Abstract Background Cerebral stroke (CS) is the leading cause of death in China, and a complex disease caused by both alterable risk factors and genetic factors. This study intended to investigate the association of MMP3, MMP14, and MMP25 single nucleotide polymorphisms (SNPs) with CS risk in a Chinese Han population. Methods A total of 1,348 Han Chinese were recruited in this case-control study. Four candidate loci including rs520540 A/G and rs679620 T/C of MMP3, rs2236302 G/C of MMP14, and rs10431961 T/C of MMP25 were successfully screened. The correlation between the four SNPs and CS risk was assessed by logistic regression analysis. The results were analyzed by false-positive report probability (FPRP) for chance or significance. The interactions between four SNPs associated with CS risk were assessed by multifactor dimensionality reduction (MDR). Results rs520540 A/G and rs679620 C/T SNP in MMP3 were associated with risk of CS in allele, codominant, dominant and log-additive models. Ischemic stroke risk were significantly lower in carriers with rs520540-A allele and rs679620-T allele than those with G/G or C/C genotypes. However, rs520540-A allele and rs679620-T allele were associated with higher risk of hemorrhagic stroke. Stratified analysis showed that these two SNPs were associated with reduced risk of CS in aged < 55 years, non-smoking and non-drinking participants, and rs679620 SNP also reduced CS risk in male participants. The levels of uric acid, high-density lipoprotein cholesterol, and eosinophil were different among patients with different genotypes of rs520540 and rs679620. No statistically significant association was found between MMP14 rs2236302 G/C or MMP25 rs10431961 T/C with CS even after stratification by stroke subtypes, age, gender as well as smoking and drinking conditions in all the genetic models. Conclusion MMP3 rs520540 A/G and rs679620 C/T polymorphisms were associated with CS risk in the Chinese Han population, which provides useful information for the prevention and diagnosis of CS.